Correlations between Maternal Knowledge, Attitude, and Posyandu Utilization on Nutritional Status in Children Under Five - Prasticha, Anggraini Dian; Sampurna, Mahendra Tri Arif; Dewanti, Linda (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: Malnutrition is a condition of deficiency, excess, or imbalance of nutrients from the amount of nutrients needed by the body. One of the ways to prevent malnutrition is by monitoring regularly through a program of public health activities, namely weighing toddlers. This study aims to determine the relationship between mother's knowledge, mother's attitude, and utilization of integrated health post (posyandu) in weighing toddlers with toddlers' nutritional status. Subjects and Method: A cross-sectional study was conducted in Semambung Village, Wonoayu District, Sidoarjo Regency, in August 2022. A total of 144 mothers and their children was selected using a proportionate stratified random sampling. The dependent variable is nutritional status. The independent variables are knowledge, mother's attitude, and posyandu utilization. The data were collected by a questionnaire. Data were analyzed by Chi square test and Odds ratio (OR). Results: Maternal irregular visit at integrated health post were at risk for having underweight (WAZ) (OR= 3.39; 95% CI= 1.46 to 7.84; p= 0.003) and stunted (WHZ) children (OR= 4.37; 95% CI= 1.20 to 15.84; p= 0.016). Conclusion: It can be concluded that there is no relationship between mother's knowledge, mother's attitude and nutritional status of toddlers. and there is a relationship between posyandu utilization and the nutritional status of children under five based on the WAZ and WHZ indexs. Keywords: knowledge, attitude, posyandu utilization, nutritional status. Correspondence:Anggraini Dian Prasticha. Midwifery Program Study, Faculty of Medicine, Airlangga University, Indonesia, Jl. Mayjen Pro. Dr. Moestopo No. 47, Pacar Kembang, Tambaksari, Surabaya, East Java 60132, Indonesia. Email: anggraini.dian.prasticha-2019@fk.unair.ac.id. Mobile: +6281235205296.